Live-Cell Imaging of Salmonella Typhimurium Interaction with Zebrafish Larvae After Injection and Immersion Delivery Methods - (:unkn) unknown (ELSEVIER SCIENCE BV, 2017)
The zebrafish model has been used to determine the role of vertebrate innate immunity during bacterial infections. Here, we compare the in vivo immune response induced by GFP-tagged Salmonella Typhimurium inoculated by immersion and microinjection in transgenic zebrafish larvae. Our novel infection protocols in zebrafish allow live-cell imaging of Salmonella colonization. (C) 2017 Elsevier B.V. All rights reserved.